2010
DOI: 10.1073/pnas.0914202107
|View full text |Cite
|
Sign up to set email alerts
|

Dental maturational sequence and dental tissue proportions in the early Upper Paleolithic child from Abrigo do Lagar Velho, Portugal

Abstract: Neandertals differ from recent and terminal Pleistocene human populations in their patterns of dental development, endostructural (internal structure) organization, and relative tissue proportions. Although significant changes in craniofacial and postcranial morphology have been found between the Middle Paleolithic and earlier Upper Paleolithic modern humans of western Eurasia and the terminal Pleistocene and Holocene inhabitants of the same region, most studies of dental maturation and structural morphology h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 38 publications
5
54
1
1
Order By: Relevance
“…Interestingly, after the inclusion of femoral diaphysis length in the models, the development of the first molar remains underestimated (i.e., its M1 development is relatively advanced), whereas the development of the second incisor, both premolars and second molar remains overestimated (i.e., its I2, P3, P4, and M2 development is relatively delayed). These results provide further support to the observed combination of delayed incisor and advanced molar development noted in Neanderthal and anatomically modern fossil human subadults (Bayle et al, ). However, the divergence between the relative development of the first and second molar is not typical of Neanderthals, and neither is delayed premolar development (Reid et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, after the inclusion of femoral diaphysis length in the models, the development of the first molar remains underestimated (i.e., its M1 development is relatively advanced), whereas the development of the second incisor, both premolars and second molar remains overestimated (i.e., its I2, P3, P4, and M2 development is relatively delayed). These results provide further support to the observed combination of delayed incisor and advanced molar development noted in Neanderthal and anatomically modern fossil human subadults (Bayle et al, ). However, the divergence between the relative development of the first and second molar is not typical of Neanderthals, and neither is delayed premolar development (Reid et al, ).…”
Section: Discussionsupporting
confidence: 81%
“…Where the corresponding Lagar Velho tooth is concerned, they found it to be intermediate between Neandertals and modern humans in crown outline, and described this fi nding as corroborating the similar conclusion derived by Bayle et al ( 2010 ) from tissue proportions. Benazzi et al ( 2012 ) also found that the crown outlines of three other fossils, two Neandertals and one Upper Paleolithic modern, were misclassifi ed by the predictive tool derived from the observed patterns.…”
Section: Tooth Morphologysupporting
confidence: 67%
“…Nevertheless, there may be some intermediate fossils, possibly reflecting the interbreeding that we now know to have occurred through the DNA evidence reviewed above. Probably the best-known case is represented by the child discovered at the Abrigo do Lagar Velho, Portugal (Duarte et al, 1999), which has been interpreted as a Neandertal-modern human hybrid dating from about 24 kya (Duarte et al, 1999; Trinkaus and Zilhão, 2003), an interpretation apparently supported by the recent analysis of its pattern of dental development (Bayle et al, 2010) 7 . Given the burial context, it has been argued that the child had been accepted as a full member of the community speculating that this type of admixture was viewed as tolerable at least, and was frequent enough to gain social acceptance (Zilhão and Trinkaus, 2003).…”
Section: The Similarities and Differences Between Neandertals And Modmentioning
confidence: 97%